Aqueous extract of Tetracarpidium conophorum increases FSH and LH plasma levels and impairs sperm indices in albino wistar rats (International Journal of Biomedical Research, 2014)
Objective: This study sought to investigate the effects of Tetracarpidium conophorum on male fertility indices. Materials and methods: Eighteen albino wistar rats between 178g to 241g were used; randomly assigned into 3 groups. Group 1 was the control group; oral gavaged 5ml of distilled water, group 2 and group 3 were administered medium dose (14.14mg/kg) and high dose (21.21mg/kg) of Tetracarpidium conophorum for 21 days. Acute toxicity study was done and the LD50 was gotten to be 1581.14mg/kg body weight. Animals were sacrificed on the 22nd day, blood samples were obtained by cardiac puncture and blood serum was obtained for hormonal assay and the testes were harvested for sperm analysis. Results: Significant increases were observed for FSH and LH in both the medium and high doses group compared to the control group. A significant decrease in fast progressive movement in medium dose and high dose compared to control group; a significant dose dependent decrease in high dose group compared to medium dose group. There was a significant decrease in percentage sperm concentration in medium dose and high dose compared to the control group and a significant increase in high dose compared to the medium dose group. In percentage normal sperm morphology, there was a significant decrease in medium dose group and high dose compared to control group, a significant increase in high dose compared to medium dose. Conclusion: Tetracarpidium conophorum adversely affect sperm characteristics; though it appears to promote biosynthesis of FSH and LH. Its potential to enhance fertility is therefore in doubt.